Silencing NTPDase3 activity rehabilitates the osteogenic commitment of post-menopausal stem cell bone progenitors - José Bernardo Noronha-Matos; Rui Pinto-Cardoso; Catarina Bessa-Andrês; Maria Teresa Magalhães-Cardoso; Fátima Ferreirinha; Maria Adelina Costa; José Marinhas; Rolando Freitas; Rui Lemos; Adélio Vilaça; António Oliveira; Julie Pelletier; et al. (Stem Cell Research & Therapy, 2023)
Abstract Background Endogenously released adenine and uracil nucleotides favour the osteogenic commitment of bone marrow-derived mesenchymal stromal cells (BM-MSCs) through the activation of ATP-sensitive P2X7 and UDP-sensitive P2Y6 receptors. Yet, these nucleotides have their osteogenic potential compromised in post-menopausal (Pm) women due to overexpression of nucleotide metabolizing enzymes, namely NTPDase3. This prompted us to investigate whether NTPDase3 gene silencing or inhibition of its enzymatic activity could rehabilitate the osteogenic potential of Pm BM-MSCs. Methods MSCs were harvested from the bone marrow of Pm women (69 ± 2 years old) and younger female controls (22 ± 4 years old). The cells were allowed to grow for 35 days in an osteogenic-inducing medium in either the absence or the presence of NTPDase3 inhibitors (PSB 06126 and hN3-B3s antibody); pre-treatment with a lentiviral short hairpin RNA (Lenti-shRNA) was used to silence the NTPDase3 gene expression. Immunofluorescence confocal microscopy was used to monitor protein cell densities. The osteogenic commitment of BM-MSCs was assessed by increases in the alkaline phosphatase (ALP) activity. The amount of the osteogenic transcription factor Osterix and the alizarin red-stained bone nodule formation. ATP was measured with the luciferin-luciferase bioluminescence assay. The kinetics of the extracellular ATP (100 µM) and UDP (100 µM) catabolism was assessed by HPLC Results The extracellular catabolism of ATP and UDP was faster in BM-MSCs from Pm women compared to younger females. The immunoreactivity against NTPDase3 increased 5.6-fold in BM-MSCs from Pm women vs. younger females. Selective inhibition or transient NTPDase3 gene silencing increased the extracellular accumulation of adenine and uracil nucleotides in cultured Pm BM-MSCs. Downregulation of NTPDase3 expression or activity rehabilitated the osteogenic commitment of Pm BM-MSCs measured as increases in ALP activity, Osterix protein cellular content and bone nodule formation; blockage of P2X7 and P2Y6 purinoceptors prevented this effect. Conclusions Data suggest that NTPDase3 overexpression in BM-MSCs may be a clinical surrogate of the osteogenic differentiation impairment in Pm women. Thus, besides P2X7 and P2Y6 receptors activation, targeting NTPDase3 may represent a novel therapeutic strategy to increase bone mass and reduce the osteoporotic risk of fractures in Pm women.